Analisis Pengaruh Harga, Kualitas Produk dan Promosi Penjualan Terhadap Keputusan Pembelian - Sabda Dian Nurani Siahaan; Aurora Elise Putriku (Forum Kerjasama Pendidikan Tinggi, 2021)
The purpose of the research is to find out the impact of Price, Product Quality, and Sales Promotion on Consumer Purchasing Decisions at KFC restaurant Sun Plaza Medan. This study is descriptive quantitative research and the data was collected through questionnaires distributed to 100 respondents. The sampling technique is simple Non Probability Sampling and this research was conducted in October - December 2020. The data analysis method used is multiple linear regression analysis. The results of this study showed: (1) Price (X1) has a positive and significant impact on Purchasing Decisions (Y); (2) Product Quality (X2) positively and significantly affects Purchasing Decisions (Y); (3) Sales Promotion (X3) positively and significantly affects Purchasing Decisions (Y); (4) and the Price, Product Quality, and Sales Promotion simultaneously have a positive and significant effect on Consumer Purchasing Decisions.